Some fractional integral inequalities of type Hermite–Hadamard through convexity - Farooq Ahmad (2019)
In the present article, the authors have established some Hermite–Hadamard type integral inequalities via Riemann–Liouville fractional integrals that generalize Hermite–Hadamard type inequalities and a few other results (Dragomir and Agarwal in Appl. Math. Lett. 11(5):91–95,1998; Dragomir, Chob and Kimc in J. Math. Anal. Appl. 245(2):489–501,2000; Yang, Hwang and Tseng in Comput. Math. Appl. 47(2–3):207–216,2004).